One size doesn't fit all: Plurality of social norms and saving behavior in Kenya - Hanna Fromell; Daniele Nosenzo; Trudy Owens; Fabio Tufano (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
We measure the social norms of sharing income with kin and neighbors in villages in Kenya. We find a plurality of norms: from a strict norm prohibiting wealth accumulation to a norm facilitating saving. Several individual and social network characteristics predict the norms upheld; the pro-saving norm becomes majoritarian when an individual can conceal their income from kin and neighbors. Whether income secrecy facilitates savings depends on the type of norm individuals uphold: stricter norm supporters are helped by secrecy, pro-saving norm supporters are harmed. This highlights the importance of measuring social norms when devising pro-saving policy interventions.
Keywords: C91; C93; D91; O12; O17; 330; Sharing norms; forced solidarity; social pressure; savings; social norms; Krupka-Weber method; lab-in-the-field experiment